2003
DOI: 10.1189/jlb.0702356
|View full text |Cite
|
Sign up to set email alerts
|

Basophils express a type 2 cytokine profile on exposure to proteases from helminths and house dust mites

Abstract: The proteolytic activities frequently associated with sources of allergens and parasite secretions have been suggested as important immunomodulators. We have investigated whether the protease activity of the house dust mite allergen Der p1 and the secreted proteases of the hookworm Necator americanus are able to directly induce type 2 cytokine production by basophils. Der p1 and the secretions of N. americanus induced interleukin (IL)-4, IL-5, and IL-13 but not interferon-gamma mRNA in KU812 basophils. Enzyme-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
106
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(110 citation statements)
references
References 35 publications
1
106
0
3
Order By: Relevance
“…In contrast, other studies rather suggested that ASP treatment leads to partially matured DCs, driving a Th2 cell polarization with IL-4 and IL-5 production (68) and allergic lung inflammation in mice (69). Reasons for these discrepancies are presently unclear but could be due to fungal strain differences or to the impact of ASP on other cells beyond DCs, such as basophils or epithelial cells, which in those experimental systems could contribute to Th2 polarization (70)(71)(72).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, other studies rather suggested that ASP treatment leads to partially matured DCs, driving a Th2 cell polarization with IL-4 and IL-5 production (68) and allergic lung inflammation in mice (69). Reasons for these discrepancies are presently unclear but could be due to fungal strain differences or to the impact of ASP on other cells beyond DCs, such as basophils or epithelial cells, which in those experimental systems could contribute to Th2 polarization (70)(71)(72).…”
Section: Discussionmentioning
confidence: 98%
“…However, since certain allergen and helminth antigens may directly crosslink FcεRI on basophils without the need for specific IgE [34][35][36], these responses may also be enhanced by the presence of TLR ligands at the same time, and TLR activation of basophils may thus contribute to enhanced cytokine production in primary immune responses against helminths as well.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro stimulation of human basophils with Der p 1 induces IL-4 expression (23), and Sokol et al (14) reported that the Th2 differentiation induced by papain in mice is mediated by IL-4 derived from papainstimulated basophils. However, Tang et al (17) proposed a reactive oxygen species-mediated model of papain-induced Th2 immune responses, in which basophils act as an amplifier rather than an initiator, and Hammad et al (24) reported that the true initiator of the HDM-induced Th2 response is not basophils, but inflammatory dendritic cells.…”
mentioning
confidence: 99%